Analisis Pemanfaatan Media Sosial Dalam Meningkatkan Penjualan di Toko Baju UD Rusli Central Kota Gunungsitoli - Meniati Harefa; Emanuel Zebua; Serniati Zebua; Yuterlin Zalukhu (Lembaga Pengembangan Kinerja Dosen, 2024)
Marketing is a comprehensive and integrated and planned activity process carried out by an institution or organization in running a business in order to meet market needs by making products that have selling value, setting prices, communicating and must distribute through exchange activities to satisfy consumers and companies. Sales are one of the marketing activities in an effort to deliver products to the market and sellers are required to influence prospective buyers so that consumers are willing to provide the products offered. Social media is content containing information managed by people who utilize publishing technology, very easy to access and to facilitate communication, influence and interaction with others and with the public or openly. This study uses a qualitative descriptive research type, namely analyzing comparisons based on data and information in the form of oral sentences obtained from research objects, then drawing research conclusions based on the data and information obtained. From the results of the study, it is known that the following things are known, the Rusli Central Store, Gunungsitoli City has utilized Instagram social media as a means of promotion, the purpose of promotion through Instagram is to be easily recognized or known by many people. Features that are often used by Rusli Central store are multiple image & video posts simultaneously with a maximum of 10 pieces, the income after using the Instagram application as a means of promotion has increased every year, visitors/followers have increased, the internet network is less stable when posting, lack of understanding of social media marketing.